Expansion of the known host range of Giardia duodenalis and Cryptosporidium spp. in captive wildlife at Beijing Zoo - Zhao Qianming; Pei Zhiyang; He Yongqiang; Jia Ting; Zhang Yanzhen; Zheng Mengjun; Zhang Zhenjie; Qi Meng (Parasite)
Giardia duodenalis and Cryptosporidium spp. are significant zoonotic parasites that cause diarrhea and affect a diverse range of hosts. This study aimed to investigate the infection rates of these parasites in captive wildlife at Beijing Zoo. A total of 445 fecal samples were collected and analyzed using PCR. The infection rate of G. duodenalis was 3.82% (17/445), with assemblage A (n = 1), assemblage B (n = 13), and assemblage E (n = 3) identified. The infection rate of Cryptosporidium spp. was 0.22% (1/445), with only one instance of C. ryanae identified from cattle (Bos taurus). To the best of our knowledge, this study enhances the understanding of the host range of G. duodenalis in captive wildlife within China, highlighting infections in Corsac Fox (Vulpes corsac), Indian Rhinoceros (Rhinoceros unicornis), and Giraffe (Giraffa camelopardalis). These findings indicate that the infection rates of G. duodenalis and Cryptosporidium spp. in captive wildlife at Beijing Zoo are low, while showing that the known host range of G. duodenalis is expanding.